Endem Types Of Mountainous Central Asia Province In Kuhitang Floor - Ibragimov A.J.; Mateen Ahmad Farid (Zien Journals, 2021)
The Surkhan oasis is very rich and colorful in the flora. However, plants are not evenly distributed throughout the globe. Plants that grow in one place may not grow elsewhere. At present, about half of the 4,500 hectares of wild plant species in the country are distributed in the oasis, and about 200 hectares of them are currently in need of serious protection. Among them, rare, endemic and relict types are the most common. Endemic types are distributed in a very small area only in one area and are not found in other areas at all. At the same time, the range of many endemic species is shrinking and their populations are declining. The diversity of the flora in South-West Gissar district and the abundance of relict, endemic and rare taxa in the Western Pamir occupy a special place in the Alai
Keywords: Kuhitang floor; Kohitang ridge; Endemism flora to Kohitang; Lepidolopha fedtschenkoana